Renaming of the genus Flavivirus to Orthoflavivirus and extension of binomial species names within the family Flaviviridae - Postler, Thomas S.; Beer, Martin; Blitvich, Bradley J.; Bukh, Jens; de Lamballerie, Xavier; Drexler, J. Felix; Imrie, Allison; Kapoor, Amit; Karganova, Galina G.; Lemey, Philippe; Lohmann, Volker; Simmonds, Peter; et al. (Archives of virology, 2023)
This review provides a summary of the recently ratified changes to genus and species nomenclature within the virus family Flaviviridae along with reasons for these changes. First, it was considered that the vernacular terms "flaviviral", "flavivirus", and "flaviviruses" could under certain circumstances be ambiguous due to the same word stem "flavi" in the taxon names Flaviviridae and Flavivirus; these terms could either have referred to all viruses classified in the family Flaviviridae or only to viruses classified in the included genus Flavivirus. To remove this ambiguity, the genus name Flavivirus was changed to Orthoflavivirus by the International Committee on Taxonomy of Viruses (ICTV). Second, all species names in the family were changed to adhere to a newly ICTV-mandated binomial format (e.g., Orthoflavivirus zikaense, Hepacivirus hominis) similar to nomenclature conventions used for species elsewhere in biology. It is important to note, however, that virus names remain unchanged. Here we outline the revised taxonomy of the family Flaviviridae as approved by the ICTV in April 2023.